Avanços e limitações da produção, armazenamento e transporte de hidrogênio verde - dos Santos Puga, Mariana; Olortiga Asencios, Yvan Jesus (Latin American Journal of Energy Research, 2023)
The search for clean sources of energy and production is one of the main objectives of countries around the world for the decarbonization of the economy. Currently, several solutions are being developed for environmental, social, and economic problems related to greenhouse gas emissions. Green hydrogen presents itself as one of the promising technologies to meet the energy demands and production processes of various sectors of the economy. Hydrogen is the most abundant chemical element on the Earth’s surface and is normally associated with organic compounds such as hydrocarbons, furthermore, hydrogen is part of water molecules. However, to obtain it in isolation, it is necessary to extract it from sources such as water, oil, natural gas, biogas, among others. Green hydrogen is produced from the electrolysis of water with energy from renewable sources. There are still some challenges to be overcome in order to effectively meet the demands of the fertilizer, oil, metallurgical, and electricity supply industries. Therefore, this work addresses the advances and limitations for the production, storage and transport of green hydrogen, as well as the international scientific production through a systematic literature review. For production, the cost of renewable energy was relevant, considering only photovoltaic energy/purchase. Mapping other options can make the analysis comprehensive. The electrolysis of water is associated with the maturity of technology and the cost of electrolysers, which are composed of high added value metals. Thus, the development of new materials is necessary. Regarding storage, the techno-economic viability of the operation is costly. Technologies that can overcome these challenges can optimize the supply chain. Several studies considered the use of the existing pipeline network for transportation. However, as countries are being considered potential export hubs, it was expected to find articles that addressed long-distance transport.